Improvement Strategy of Porong Kanal Irrigation Network Performance in Delta Brantas Irrigation Area with Swot Analysis (Strength, Weakness, Opportunities, and Threats) - Fitri, Melani; Wardoyo, Wasis; Sri S., Theresia (IPTEK Journal of Proceedings Series, 2017)
Delta Brantas Irrigation Area with total covering irrigated area 21,984 Ha, located entirely in Sidoarjo. Irrigation system performance in Delta Brantas Irrigation Area especially in Porong Kanal Primary Network tended to decline. So improvement strategy required in order to provide better irrigation services that fit the needs of the farming community. This problem can be studied by analyzing the existing condition, determining priority handling factors and a strategy for improving the irrigation network performance. From research results indicated that the degradation of the irrigation system performance in Delta Brantas Irrigation Area from 2012 to 2014 amounted to 3.66%. The priority handling factors that influencing the performance of Delta Brantas irrigation network are the condition of regulator structures, conditions of complementary structures, sewer condition, the completeness of operation and maintenance equipment, total personnel of operation and maintenance, personnel assignment of the operation and maintenance, legal status GP3A/P3A, institutional conditions of P3A, and P3A actively in search of irrigation networks, and P3A contribution to repair the irrigation networks. From SWOT analysis resulted a strategy position used to improve the performance of Porong Kanal Irrigation Network Delta Brantas Irrigation Area is turn-around strategy which minimizing the weaknesses to take advantage of opportunities.